Characterization and Classifications of Saline/Sodic Soils of Ambo Area of Irrigated Farm Land in Golina Watershed in Raya Valley, Amhara Region, Ethiopia - ashebir, merse mengesha; W, Lemma; T, Solomon (International Journal on Food, Agriculture and Natural Resources, 2024)
All soils are known to contain a certain amount of soluble salts and exchangeable sodium, magnesium, potassium, and calcium. However, excessive enrichment of any one of them can interfere with many soil processes, including plant growth, and the effects depend on the degree of enrichment and the type of plant. Therefore, the objective of this study was to characterize the salt-affected soils of the Ambo area for irrigated farmlands in the Golina Watershed in Raya Kobo Woreda, Amhara region. One profile was excavated from an irrigated field to carry out this activity. One profile was excavated from the irrigated field to conduct this activity. Ten soil samples were taken from the soil profile at 2 m depth at 20 cm depth intervals. The samples were analyzed for several soil physical properties, including soil pH, soluble cations and anions, soluble salts (electrical conductivity, EC), exchangeable cations (Ca, Mg, Na, K), total nitrogen, organic carbon, soluble phosphorus, percent exchangeable sodium, sodium absorption, and soil physical properties (soil color, texture, bulk density, and soil porosity). Chemical properties were also analyzed. The analysis showed that the irrigated farmland soils had a pH of 7.6 to 8.8, electrical conductivity of 1.3 to 14 dsm-1, organic carbon of 0.3 to 1.2%, total nitrogen of 0.11 to 0.35%, soluble phosphorus of 24 to 41.4 mg kg-1, and cation exchange capacity of 50.3 to 65.5 cmol(+) kg-1. The distribution of exchangeable calcium was not consistent across the soil profiles of the irrigated farmlands. In general, the top layer of soil at both sites (because of its agricultural use) was considered for EC, ESP, and pH values. The irrigated farmland soils were classified as saline soils.